1984
DOI: 10.1002/jmv.1890140210
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus and vesicular stomatitis virus replication in the presence of 6‐diazo‐5‐oxo‐L‐norleucine or 2‐deoxy‐D‐glucose

Abstract: The effects of 6-diazo-5-oxo-L-norleucine (DON), 2-deoxy-D-glucose (DOG), and tunicamycin (TM) on the replication of poliovirus (PV) and vesicular stomatitis virus (VSV) were examined. During a 48-hr replication period, TM, DON, and DOG inhibit VSV plaque formation in HEp-2 cells by 99.9%, 99.8%, and 99.9% respectively. Inhibition of VSV by DON is reversed with glutamine. Although all three agents are known to affect glycoprotein synthesis, DON and DOG also inhibit plaque formation of viruses devoid of structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…It was suggested that the hydrophobic domain of 3A might span the lipid bilayer and that N-glycosylation of 3A-containing proteins might play a functional role during poliovirus infection. In the present study, however, we report that tunicamycin, an inhibitor of N-glycosylation, has no effect on poliovirus yield, in agreement with previous reports (17,27), arguing that the glycosylation of 3A and 3AB observed in vitro is not relevant to the biology of the virus.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…It was suggested that the hydrophobic domain of 3A might span the lipid bilayer and that N-glycosylation of 3A-containing proteins might play a functional role during poliovirus infection. In the present study, however, we report that tunicamycin, an inhibitor of N-glycosylation, has no effect on poliovirus yield, in agreement with previous reports (17,27), arguing that the glycosylation of 3A and 3AB observed in vitro is not relevant to the biology of the virus.…”
supporting
confidence: 93%
“…These authors (18) also suggested that the inhibition of poliovirus by brefeldin A (BFA), an inhibitor of transport through the secretory pathway, might stem from the resulting inhibition of Golgi-specific oligosaccharide modifications in BFA-treated cells. Two pieces of data argued against this hypothesis: glycosylated forms of 3A and 3AB were not detected in extracts of poliovirus-infected cells (18), and tunicamycin had been reported to have no effect on poliovirus infection, although little documentation of these experiments was actually published (17,27). Due to the fragmentary nature of the previous tunicamycin experiments, and the possible significance of the in vitro glycosylation of poliovirus proteins, we tested the effect of tunicamycin on poliovirus growth under conditions in which tunicamycin was shown to be active.…”
Section: Resultsmentioning
confidence: 99%
“…Goldstein and Guskey [7], demonstrated that the replication of both poliovirus and vesicular stomatitis virus (VSV) could be inhibited by DON and the inhibitory effect was reversed by the addition of glutamine to the cultures. More recently, Nishio et al [ 15], have demonstrated that DON can inhibit the replication of human parainfluenza virus type 2 (HPIV-2), mumps and VSV, at concentrations that were not toxic to the host cells and did not inhibit host cell macromolecular synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The replication of both poliovirus and vesicular stomatitis virus (VSV) has been shown to be inhibited by 6-diazo-5-oxo-L-norleucine (DON), the inhibitory effect was reversed by the addition of glutamine to the cultures [7]. Furthermore, the replication of the Moloney leukaemia virus has been inhibited in cultures deficient in glutamine and isoleucine [6], while more recently DON has been used to inhibit the replication of human parainfluenza virus type 2 (HPIV-2), mumps and VSV at concentrations which were not toxic to host cells [15].…”
Section: Introductionmentioning
confidence: 99%